Frosting Effect on Potato and its management - Singh, S. P.; Sadawarti, Murlidhar J.; Pandey, K. K.; Singh, B. P. (Indian Farming, 2015)
Potato is very much susceptible to frost which is an abiotic constraint causing severe yield losses. Frost damage also affects growth of nucleus and breeder seed potato crops under irrigated conditions. The effectiveness of furrow irrigation has been reported to prevent frost damage in potato to a large extent.